MODEL OF THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE TOWARDS COVID-19 PREVENTION PRACTICES DURING INSTRUCTIONS (Study on Students and Students of SMA Pondok Pesantren Islamic Association of 67 Objects in Tasikmalaya City in 2021) - Asep Suryana Abdurrahmat; Dian Saraswati; Rian Arie Gustaman (Gorontalo State University, 2022)
Covid-19 merupakan salah satu pandemi yang belum berakhir di Dunia. Penularannya berjalan cukup cepat hingga mengakibatkan peningkatan jumlah kasus dengan kasus kematian yang tidak sedikit. Kota Tasikmalaya termasuk kedalam wilayah Jabar dengan status wilayah beresiko sedang dan berstatus siaga darurat Nomor: 443/Kep.176-Dinkes/2020. Salah satu penyebab tingginya kasus di kota Tasikmalaya adalah adanya Klaster Pesantren dan salah satu yang tertinggi adalah Pesantren Persatuan Islam 67 Benda yang berada di Kecamatan Cipedes. Covid-19 erat kaitannya dengan praktek. Perlindungan bagi anak-anak dan fasilitas-fasilitas pendidikan sangatlah penting. Diperlukan kewaspadaan untuk mencegah kemungkinan penyebaran Covid-19 di sekolah. Kebaruan penelitian ini karena meneliti tentang model hubungan pengetahuan dan sikap terhadap praktek pencegahan Covid-19 selama di pesantren. Tujuan penelitian ini untuk mengetahui Model Hubungan Pengetahuan dan sikap terhadap praktek pencegahan Covid-19 selama di Pondok Pesantren Persatuan Islam 67 Benda Kota Tasikmalaya. Metode penelitian ini adalah kuantitatif yaitu model hubungan pengetahuan dan sikat terhadap praktek dengan desain penelitian cross sectional. Populasi total adalah 397 santri dan sampel berjumlah 157 santri SMA Pondok Pesantren Persatuan Islam 67 Benda Kota Tasikmalaya.Teknik sampel yang digunakan pada penelitian ini adalah probability sampling, sampel diambil dari setiap kelas dengan teknik proportional random sampling. Mengunakan analisi multivariat. Hasil penelitian menunjulan bahwa setiap peningkatan pengetahuan responden tentang pencegahan Covid maka praktik pencegahan covid semakin meningkat, kemudian setiap peningkatan sikap responden tentang pencegahan Covid maka praktik pencegahan covid semakin meningkat. Kesimpulan Pengetahuan dan sikap menpengaruhi pencegahan covid- 19. Kata Kunci: Pengetahuan; Sikap; Praktek pencegahan; Covid-19.AbstractCovid-19 is a pandemic that has not ended in the world. The transmission is running fast enough to cause an increase in the number of cases with not a few deaths. The city of Tasikmalaya is included in the West Java region with the status of a medium risk area and an emergency alert status Number: 443/Kep.176- Dinkes/2020. One of the causes of the high number of cases in the city of Tasikmalaya is the existence of the Islamic Boarding School Cluster and one of the highest is the 67 Benda Islamic Boarding School located in Cipedes District. Covid-19 is closely related to practice. Protection of children and educational facilities is very important. Vigilance is needed to prevent the possible spread of COVID-19 in schools. The novelty of this research is because it examines the model of the relationship of knowledge and attitudes towards covid-19 prevention practices while in Islamic boarding schools. The purpose of this study was to determine the Knowledge Relationship Model and attitude towards the practice of preventing Covid-19 while at the Islamic Unity Islamic Boarding School 67 Benda, Tasikmalaya City. This research method is quantitative, namely the model of the relationship between knowledge and practice with a cross sectional research design. The total population is 397 students and the sample is 157 students of SMA Pondok Pesantren Persatuan Islam 67 Benda, Tasikmalaya City. The sample technique used in this study is probability sampling, the sample is taken from each class by proportional random sampling technique. Using multivariate analysis. The results of the study show that for every increase in respondents' knowledge about Covid prevention, the practice of preventing Covid increases, then every time the respondent's attitude increases about preventing Covid, the practice of preventing Covid will increase.Conclusion Knowledge and attitudes affect the prevention of covid-19Keywords: Knowledge, Attitude; Practice of preventing; Covid-19